Barriers to Graduate Applications: Perspectives of Undergraduate Students From Underrepresented Backgrounds in Communication Science and Disorders. - Lugo, Victor Alan; Wood, Carla; Torres-Chavarro, Michelle; Garcia-Salas, Miguel (Perspectives of the ASHA Special Interest Groups, 2023)
Purpose: The purpose of this preliminary study was to examine the perspectives of students from underrepresented backgrounds on the graduate school application process and identify ways to improve diversity, equity, inclusion, and accessibility in communication science and disorders. Method: A novel 15-item survey was used to solicit information about the experiences and perspectives of the graduate application process from 39 senior undergraduate students in a communication science and disorders program. Semistructured interviews were then conducted with seven students from underrepresented backgrounds to further explore perceived barriers to graduate applications and potential resources and supports. Results: Results demonstrated a variety of factors, including financial demands, Graduate Record Examinations requirements, and program location and prestige, that influenced student decision making during the application process. Students from underrepresented backgrounds reported applying to more programs on average but engaged in numerically fewer hours of research and practicum experiences than peers from majority backgrounds. The most significant barriers to the graduate application process included learning and mentorship challenges during COVID-19, limited experiential learning opportunities, and difficulties forming social connections. Departmental support, application assistance, and mentorship initiatives were highlighted as potential levers of change. Conclusions: Based on reported barriers to the graduate application process, more research is necessary to further investigate the extent these factors influence achievement, retention, and overall success of students from underrepresented backgrounds. Additional resources and supports, especially those recommended by students in this study, may serve as potential action steps to improve diversity, equity, inclusion, and accessibility in communication science and disorders programs. Supplemental Material: https://doi.org/10.23641/asha.23519058